Business Development of Lie Tulip Salon Using a Canvas Business Model - Sylvia, Monica; Sumadhinata, Yelli Eka (Technium Social Sciences Journal, 2021)
This research focuses on Lie Tulip Salon and Spa which works in the field of beauty salon services and beauty treatments. This study aims to examine the application of the canvas business model at Lie Tulip’s salons and spas. This research is a qualitative descriptive study that describes the Canvas Business Model at Lie Tulip’s salon and spa using SWOT analysis. The data collection method was carried out by conducting interviews and taking documentation. The results of this study prove that the consumer segmentation in this company is female consumers with an average age of 15-60 years. In addition, the channel operated by this company is to build good communication with its customers, and to provide the best and professional service. Lie tulip salon and spa always conducts service standardization training for its employees. Furthermore, this company can establish good relationships with the suppliers of cosmetic products. Finally, the cost structure in this company shows that the biggest cost factor in the company is the salary of the experts.